Autophagy in stem cell aging - Revuelta, Miren (Aging Cell, 2017)
Aging is responsible for changes in mammalian tissues that result in an imbalance to tissue homeostasis and a decline in the regeneration capacity of organs due to stem cell exhaustion. Autophagy is a constitutive pathway necessary to degrade damaged organelles and protein aggregates. Autophagy is one of the hallmarks of aging, which involves a decline in the number and functionality of stem cells. Recent studies show that stem cells require autophagy to get rid of cellular waste produced during the quiescent stage. In particular, two independent studies in muscle and hematopoietic stem cells demonstrate the relevance of the autophagy impairment for stem cell exhaustion and aging. In this review, we summarize the main results of these works, which helped to elucidate the impact of autophagy in stem cell activity as well as in age‐associated diseases.